Carbon replacement and stability changes in short-term silvo-pastoral experiments in Colombian Amazonia - Mosquera V., Octavio; Buurman, Peter; Ramírez, Bertha L.; Amézquita, María Cristina (Elsevier, 2012)
There is little information on the effects of land use change on soil Carbon stocks in Colombian Amazonia. Such information would be needed to assess the impact of this area on the global C cycle and the sustainability of agricultural systems that are replacing native forest. The aim of this study was to evaluate soil carbon stocks and changes after the clearing of the native forest, the establishment of pastures and the reclamation of the degraded pasture, in Caquetá, Colombia.